Eficiência de portos e terminais privativos brasileiros com características distintas - Bertoloto, Rodrigo Ferreira (2010)
The cargo type influences directly the characteristics of ships and port infrastructure needed to move this load. Thus, some ports are seeking the expertise of its activities or diversification depending on the loads that are moved into their installations. This study analyzes, through Data Envelopment Analysis (DEA), efficiency of public ports and terminals for exclusive use with different characteristics, ie not homogeneous DMUs (Decision Making Units), in the period 2007 to 2009. Different ports are classified into four distinct clusters and after the homogenization of DMUs a new DEA model is run with all ports and then the compensated efficiencies are obtained.